Incentivizing the Missing Middle: The Role of Economic Development Policy. Issue 2 (May 2020) - Patrick, Carlianne; Stephens, Heather M.
The shrinking middle class and increasing income polarization in the United States are issues of concern to policy makers and others. Economic development incentives are a key policy tool used at the state and local levels to promote local economic growth, and, presumably, provide employment opportunities. However, these incentives may have unintended consequences that may be contributing to the decline of the middle class. The authors combine detailed industry-level detail on incentives with proprietary county-level industry employment data and two methods for defining middle-class industries. Using an instrumental variable approach, the authors estimate how differential economic development policies affect middle-class jobs. The authors find evidence that incentivizing creative-class and high-wage industries may be contributing to the hollowing out of the middle class. Without hurting employment in other industries, targeting working-class and middle-wage industries alleviates this trend, while reducing incentives on creative-class and high-wage industries could help increase working and middle-class employment.